2019
DOI: 10.1177/1045389x19828825
|View full text |Cite
|
Sign up to set email alerts
|

Smart magnetorheological elastomer peristaltic pump

Abstract: A smart magnetorheological elastomer peristaltic pump (MRE-PP) realizes controlled movements to convey Newtonian and non-Newtonian fluids under various scheduling policies for electromagnets. Although the structure of the basic element consisted of a magnetorheological elastomer tube and an electromagnet is very succinct, the capability of fluid conveying is dramatically improved when the magnetorheological elastomer peristaltic pump composed of more elements in series is employed. Besides, scheduling policies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…This work demonstrated that sMEs could be used in valving systems for air, as well as for liquid valving. More recently, others sought to produce a peristaltic pump, utilizing the action of multiple electromagnets compressing a tube of MRE to squeeze fluid forward (Wu et al, 2019 ). The same researchers also provided a numerical analysis and framework of the performance of their designed device, attempting to model and optimize its performance (Wu et al, 2020 ).…”
Section: Reviewmentioning
confidence: 99%
“…This work demonstrated that sMEs could be used in valving systems for air, as well as for liquid valving. More recently, others sought to produce a peristaltic pump, utilizing the action of multiple electromagnets compressing a tube of MRE to squeeze fluid forward (Wu et al, 2019 ). The same researchers also provided a numerical analysis and framework of the performance of their designed device, attempting to model and optimize its performance (Wu et al, 2020 ).…”
Section: Reviewmentioning
confidence: 99%
“…In the numerical study, the magneto-fluid–solid interaction (MFSI) should be elucidated first. The magnetization curve (Wu et al, 2017; 2019a; 2019b) and Mooney–Rivlin model (Sun et al, 2014; Yang et al, 2017; Yu and Zhao, 2009) are utilized to represent magnetic-induced body force, and the equilibrium and constitutive equations of a mass point in MRE domain are written as follows…”
Section: 2d Models Of Mre-ppsmentioning
confidence: 99%
“…Finite element mesh of the MRE-PP is depicted in Figure 1(c). The magnetic properties of the MRE tubes are the same with our previous study (Wu et al, 2019a), which is imported in COMSOL using interpolation function, as illustrated in Figure 1(d). Joint parts of neighboring MRE tubes are fixed by clamps with 2-mm width, and two ends of MRE-PPs are fastened.…”
Section: Constitutive Equationmentioning
confidence: 99%
See 2 more Smart Citations